2021
DOI: 10.1123/japa.2019-0452
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Exergaming-Based Dance Training Paradigm on Autonomic Nervous System Modulation in Healthy Older Adults: A Randomized Controlled Trial

Abstract: The purpose of this study was to determine if an exergaming-based dance training protocol can improve heart rate variability (HRV) in healthy older adults. A total of 20 healthy older adults (≥65 years old) were randomly assigned to two groups. The intervention group received an exergaming-based dance aerobic training for 6 weeks, while the control group received a 1-hr education on conventional physical exercises. Data obtained from HRV analysis pre- (Week 0) and postintervention (Week 7) consisted of high-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Regarding control groups, the mean age ranged from 58.5 [ 60 , 61 ] to 78.8 years [ 22 ]. Eight trials comprised female and male participants [ 5 , 18 , 20 , 22 , 46 , 56 , 59 , 60 ]. Four trials considered only female [ 21 , 58 , 60 , 61 ] and one study included only male participants [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding control groups, the mean age ranged from 58.5 [ 60 , 61 ] to 78.8 years [ 22 ]. Eight trials comprised female and male participants [ 5 , 18 , 20 , 22 , 46 , 56 , 59 , 60 ]. Four trials considered only female [ 21 , 58 , 60 , 61 ] and one study included only male participants [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies recorded while the participants were sitting [ 5 , 18 , 46 , 56 , 58 , 59 ]. A supine position was chosen in five studies [ 20 , 22 , 57 , 60 , 61 ] and one study did not provide any information about the position during the recording [ 21 ]. Eight studies recorded NN intervals for a fixed time range.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the HRV-related parameters, previous studies have primarily measured these parameters in a resting state and have revealed contradictory results. Indeed, a significant increase of older adults’ resting HRV has been previously reported following 6 months of aerobic exercise training (31 ± 5 ms) [ 82 ], 6 weeks [ 83 ] or 6 months [ 84 ] of exergaming-based dance training, as well as 12 months of supervised stretching and aerobic exercise training [ 85 ]. However, Jakubec et al [ 86 ] and Shen et al [ 87 ] failed to report clear HRV improvements following 6 months or 10 weeks of aerobic exercise training, respectively.…”
Section: Discussionmentioning
confidence: 99%